Liver Transplantation for Hepatitis D Virus in the United States: A UNOS Study on Outcomes in the MELD Era. Issue 1 (17th December 2021) - Kushner, Tatyana; Da, Ben L.; Chan, Aryana; Dieterich, Douglas; Sigel, Keith; Saberi, Behnam
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Without available curative therapies for delta hepatitis (hepatitis delta virus [HDV]), hepatic decompensation and hepatocellular carcinoma (HCC) among HDV patients often necessitates liver transplantation (LT). The objective of this study was to evaluate outcomes of LT among hepatitis B virus (HBV)/HDV patients in the United States. Methods: We performed the first US-based retrospective study of patients who underwent LT for HDV compared with HBV (monoinfection) in the years 2002–2019. We evaluated posttransplant survival and predictors of survival. Results: We identified a total of 152 HBV/HDV and 5435 HBV patients who underwent LT. HDV patients were younger at transplant (52 versus 55, P < 0.001), less commonly Asian (16% versus 36%, P < 0.001), more likely to be HCV Ab positive (42% versus 28%, P < 0.001), and less likely to be listed for LT with HCC (38% versus 51%, P = 0.001), more likely to have ascites (73% versus 64%, P = 0.019), had worse coagulopathy (mean INR 2.0 versus 1.82, P = 0.04), and were more likely to receive a HCV-positive donor organ (7% versus 3%, P = 0.001). Post-LT overall survival and graft survival were similar between HDV and HBV patients, including among patients with HCC. Older age, HCV coinfection, HCC, and higher model for end-stage liver disease at transplant were associated with higher posttransplant mortality. Conclusions: HDV patients were sicker and more likely to be listed for LT for decompensated disease compared with HBV patients. Post-LT survival was similar between HDV and HBV patients, in contrast to prior international studies that suggested worse post-LT survival in HBV patients due to higher rates of HBV reactivation.